Association between coffee drinking and endometrial cancer risk: A meta‐analysis. Issue 3 (19th January 2022) - Gao, Yu; Zhai, Peiling; Jiang, Fang; Zhou, Fushun; Wang, Xinbo
Abstract: Aim: Coffee drinking is considered as a risk factor of endometrial cancer (EC). Here, we conducted a meta‐analysis of observational study to evaluate the relationship between coffee drinking and the risk of EC. Methods: The MEDLINE and EMBASE databases were searched until July 2018. Pooled relative risks (RRs) with 95% confidence intervals (CIs) were calculated using a random‐effects model. Results: A total of 24 studies (12 case–control and 12 cohort studies) on coffee intake with 9833 incident cases of EC and 699 234 subjects were included in the meta‐analysis. The pooled RR of endometrial cancer for the highest versus the lowest categories of coffee intake was 0.71 (95% CI: 0.65–0.77; I 2 = 14%, p for heterogeneity = 0.26). By study design, the pooled RRs were 0.68 (95% CI: 0.56–0.83) for case–control studies and 0.70 (95% CI: 0.63–0.77) for cohort studies. For different regions, the pooled RRs were 0.74 (95% CI: 0.62–0.88) in Europe, 0.71 (95% CI: 0.64–0.79) in United States/Canada, and 0.40 (95% CI: 0.28–0.57) in Japan. By additional subgroup analysis, a stronger inverse association was shown in caffeinated coffee drinkers (RR 0.66, 95% CI: 0.52–0.83), individuals with the higher body mass index (BMI) (RR 0.65, 95% CI: 0.54–0.79), never smokers (RR 0.68, 95% CI: 0.56–0.84), ever smokers (RR 0.56, 95% CI: 0.45–0.70), and those who never used hormone replacement therapy (HRT) (RR 0.88, 95% CI: 0.79–0.98). The consumption of filtered or boiled coffee showed no significant association. Conclusions: Increased coffee intake is associated with a reduced risk of EC.